Anthropological considerations of production, exchange, vending and tourism - Wood, Donald C. (Research in economic anthropology ;, 2017)
Volume 37 of REA features eleven original articles organized in four different sections, each focusing on a specific, popular and significant theme in economic anthropology: production, exchange, vending, and tourism. The first section investigates the brewing (and selling) of homemade beer among Maragoli women in western Kenya, continuity and change in small-scale family farming in a rural part of Costa Rica, and theoretical models of the transitions to farming that marked the Neolithic Revolution. The second section, on exchange, opens with another archaeological examination of relationships between long-distance exchange and the centralization of political power in Pre-Columbian America. This section also explores adaptations of the Ten Thousand Villages fair trade organization following the recent global recession, exchanges and "productive leisure" at North Market in Columbus, Ohio, and social values in flux over problems relating to exchange amidst conditions of scarcity in the Solomon Islands. The third section investigates the plight and adaptations of vendors in a southern Chinese city and on a Mexican beach, drawing attention to the effects of both national government policies and international trade agreements on their lives. The volume closes with a section that considers important and timely issues in tourism - the role of debt in commission-based relationships between showroom owners and tour guides in Agra, India, and risk, resilience, health, and government policy in Jamaica's sex tourism industry.